Hsa_circ_0000518 Facilitates Non-Small-Cell Lung Cancer Progression via Moderating miR-330-3p and Positively Regulating SLC1A5. (15th July 2022) - Lv, Huilai; Shi, Zhihua; Sui, Aixia; Zhang, Yan; Peng, Liangbiao; Wang, Mingbo; Zhang, Fan
Abstract : Background/Aim . Non-small-cell lung cancer (NSCLC) is the principal agent of cancer deaths globally. The goal of this study was to determine how circular RNA_0000518 (circ_0000518) regulates tumor progression. Materials/Methods . circ_0000518 was selected as a study target involved in NSCLC from GEO (Gene Expression Omnibus) database. circ_0000518 level was gauged by qRT-PCR. It was confirmed as circRNA by actinomycin D inhibition and RNase R assay. Subcellular localization of circ_0000518 was identified by FISH. Cell function was determined by CCK-8, Transwell, and western blot. Glutamine metabolic factors were detected by ELISA. The target regulation relationship between genes was clarified by dual-luciferase reporter assay. In vivo models were established to evaluate the impact of circ_0000518 on tumor growth. Immunohistochemical staining for Ki67, vimentin, and E-cadherin was used to detect cell proliferation and metastasis, respectively. Results . circ_0000518 expression was enhanced in NSCLC. si-circ_0000518 inhibited cell proliferation, invasion, and glutamine metabolism. circ_0000518 functioned as a molecular sponge for miR-330-3p, and inhibition of miR-330-3p in cells markedly reversed circ_0000518 interference-mediated antitumor effects. miR-330-3p interacted with 3′ -UTR of SLC1A5. miR-330-3p inhibitor-mediated protumor effect was remarkably reversed in cells after the knockdown of SLC1A5. circ_0000518 knockdown reduced glutamine, glutamate, and α -KG by targeting miR-330-3p. Intertumoral injection of circ_0000518 shRNA adeno-associated virus effectively halted xenograft tumor growth. Conclusion . The current study revealed that circ_0000518 may have a prooncogenic function in the formation and progression of NSCLC, which might be achieved through moderating the miR-330-3p/SLC1A5 axis.